2015
DOI: 10.1111/jtxs.12114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of High‐Pressure Homogenization (HPH) on the Settling Velocity of Particles in an Alcoholic Rice Beverage Using Video Recording, Turbidity and Computational Fluid Dynamic Simulation

Abstract: High‐pressure homogenization (HPH) was applied to an alcoholic rice beverage (ARB). The effects of pressure (48–172 MPa) and the number of passes (1–3) on the fluid properties of the ARB, such as particle size, viscosity, turbidity and settling velocity, were investigated. Mean diameters continuously decreased with increasing homogenization pressure (P) and pass number (PN) until it reached a saturated condition (172 MPa with PN = 2). The viscosity and volume fraction of ARBs proportionally increased with incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The turbidity of the sample under 0 MPa was the lowest (1.06%), and that of the sample under 60 MPa was the highest (9.08%). In addition, it showed an upward trend when the homogenisation pressure was between 20 and 60 MPa, while it gradually decreased when the pressure exceeded 60 MPa ( Table 2 ), probably because smaller particles were lighter to pass through the samples as the pressure increased [ 54 ]. Studies have shown that homogenisation treatment has an impact on beverage turbidity; the turbidity change in beverages is mainly due to the fact that during the homogenisation process, the particulate matter in the beverages composed of pectin, fat, cellulose compounds, proteins, and their complexes with various substances are broken down into micron sizes to produce a stable dispersion, thus giving the juices higher turbidity [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The turbidity of the sample under 0 MPa was the lowest (1.06%), and that of the sample under 60 MPa was the highest (9.08%). In addition, it showed an upward trend when the homogenisation pressure was between 20 and 60 MPa, while it gradually decreased when the pressure exceeded 60 MPa ( Table 2 ), probably because smaller particles were lighter to pass through the samples as the pressure increased [ 54 ]. Studies have shown that homogenisation treatment has an impact on beverage turbidity; the turbidity change in beverages is mainly due to the fact that during the homogenisation process, the particulate matter in the beverages composed of pectin, fat, cellulose compounds, proteins, and their complexes with various substances are broken down into micron sizes to produce a stable dispersion, thus giving the juices higher turbidity [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Video recording analysis is a useful method for assessing the physical properties of matter and it is also an emerging method for assessing chewing behavior in oral processing (Moon & Yoon, 2015; Wilson et al, 2018). Laguna et al (2016) examined ratings of eating difficulty of various foods using frame‐by‐frame video recording analysis.…”
Section: Introductionmentioning
confidence: 99%